PROSES PENYELESAIAN SENGKETA DALAM GADAI SAHAM MELALUI LEMBAGA ALTERNATIF PENYELESAIAN SENGKETA (LAPS) SEKTOR JASA KEUANGAN - Dinda Nisa El Salwa; ' Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2024)
This article aims to find out the process of settling share pawn disputes through the Institution of Financial Services Sector Alternative Dispute Resolution (LAPS). The research method used in this article is normative juridical research, with a statue approach. The sources of law materials used in this article are primary and secondary legal materials. The result of this article, show that the pawn dispute settlement process can be carried out in 2 (two) attempts, through the court or outside the court. The Financial Services Authority (OJK) established an Institution of Alternative Dispute Resolution (LAPS) for the Financial Services Sector which integrates with several dispute resolution institutions. Alternative dispute resolution on share pledges outside the court can be done through mediation, arbitration, or adjudication through the Institution of Alternative Dispute Resolution Institution (LAPS) in Financial Services Sector.